2021
DOI: 10.1186/s10020-021-00308-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic administration of etoposide coincides with reduced systemic HMGB1 levels in macrophage activation syndrome

Abstract: Background Macrophage activation syndrome (MAS) is a potentially fatal complication of systemic inflammation. HMGB1 is a nuclear protein released extracellularly during proinflammatory lytic cell death or secreted by activated macrophages, NK cells, and additional cell types during infection or sterile injury. Extracellular HMGB1 orchestrates central events in inflammation as a prototype alarmin. TLR4 and the receptor for advanced glycation end products operate as key HMGB1 receptors to mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…HMGB1 is a damage associated molecular pattern (DAMP), which has been studied in a series of inflammatory diseases, including JIA. Highly increased levels of HMGB1 have also been reported during MAS [ 16 ]. Since HMGB1 was not included in the PEA inflammation panel, HMGB1 levels were determined by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…HMGB1 is a damage associated molecular pattern (DAMP), which has been studied in a series of inflammatory diseases, including JIA. Highly increased levels of HMGB1 have also been reported during MAS [ 16 ]. Since HMGB1 was not included in the PEA inflammation panel, HMGB1 levels were determined by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Based on experience in pHLH, the topoisomerase inhibitor etoposide has been used in IEC-HS, and is considered by some to be second-line [ 8 , 90 ]. Etoposide abrogates effector cell activity through induction of apoptosis rather than more inflammatory cell death mechanisms like pyroptosis [ 142 , 143 ]. However, avoidance of effector cell destruction is of course beneficial if possible, and etoposide causes increased risk of secondary malignancies.…”
Section: Immune Effector Cell-associated Hlh-like Syndromementioning
confidence: 99%
“…Karin Palmblad et al. found that the use of etoposide can lead to clinical improvement coinciding with a decline of systemic HMGB1, IL-18, IFN-γ, and ferritin levels ( 141 ). Although there is some evidence that this drug may aggravate the infection or make it easier to develop new infections, its benefits are obviously greater ( 140 ).…”
Section: The Attractive Therapeutic Approach To Prevent Mas In Covid-19mentioning
confidence: 99%